2009
DOI: 10.1080/08923970902785253
|View full text |Cite
|
Sign up to set email alerts
|

Gemfibrozil, stretching arms beyond lipid lowering

Abstract: Gemfibrozil is long known for its ability to reduce the level of triglycerides in the blood circulation and to decrease the risk of hyperlipidemia. However, a number of recent studies reveal that apart from its lipid-lowering effects, gemfibrozil can also regulate many other signaling pathways responsible for inflammation, switching of T-helper cells, cell-to-cell contact, migration, and oxidative stress. In this review, we have made an honest attempt to analyze various biological activities of gemfibrozil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 94 publications
(115 reference statements)
2
60
0
Order By: Relevance
“…The potential interplay between TFEB and lipid metabolism led us to investigate the role of gemfibrozil and ATRA, which are potential activators of PPAR␣ and RXR␣, respectively. Gemfibrozil, marketed as "Lopid," is an FDA-approved drug prescribed for hyperlipidemia (17,19), but it has been shown to have multiple beneficial effects (22). The ability of gemfibrozil to cross the blood-brain barrier has already been documented (20).…”
Section: Discussionmentioning
confidence: 99%
“…The potential interplay between TFEB and lipid metabolism led us to investigate the role of gemfibrozil and ATRA, which are potential activators of PPAR␣ and RXR␣, respectively. Gemfibrozil, marketed as "Lopid," is an FDA-approved drug prescribed for hyperlipidemia (17,19), but it has been shown to have multiple beneficial effects (22). The ability of gemfibrozil to cross the blood-brain barrier has already been documented (20).…”
Section: Discussionmentioning
confidence: 99%
“…2). 29) Administration of RGAP markedly reduced the up-regulated levels of NEFA, considered as a risk factor for atherosclerosis, 30,31) under Triton WR1339 treatment conditions (Fig. 2).…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have shown that antioxidant and anti-inflammatory properties of GEM could be mediated by several pathways. It has been reported that GEM effects could be mediated through PPAR-α dependent and independent pathways and it has been emphasized that antioxidative, immunomodulatory, and anti-inflammatory activities of GEM are not PPAR-α dependent (20). It has been reported that GEM resulted in reduction of TNF-α and interleukin 6, and also decreased the expression of NADPH oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…There is little data regarding the role of the Peroxisome ProliferatorActivated Receptors Alpha (PPAR-α) in lung fibrosis (16). Furthermore, GEM as a fibric acid derivative lipid lowering agent and PPAR-α receptor agonist, has some effects other than in the treatment of hyperlipidemia (17)(18)(19)(20). In previous studies, it has been well confirmed that GEM has antioxidant and anti-inflammatory properties through effects on TGF-B, TNF-α, and PPAR-α (21, 22).…”
Section: Introductionmentioning
confidence: 99%